Regulatory domain or CpG site variation in SLC12A5, encoding the chloride transporter KCC2, in human autism and schizophrenia - Merner, Nancy D.; Chandler, Madison R.; Bourassa, Cynthia; Liang, Bo; Khanna, Arjun R.; Dion, Patrick; Rouleau, Guy A.; Kahle, Kristopher T. (Frontiers in Cellular Neuroscience, 2015)
Many encoded gene products responsible for neurodevelopmental disorders (NDs) like autism spectrum disorders (ASD), schizophrenia (SCZ), intellectual disability (ID), and idiopathic generalized epilepsy (IGE) converge on networks controlling synaptic function. An increase in KCC2 (SLC12A5) Cl- transporter activity drives the developmental GABA excitatory-inhibitory sequence, but the role of KCC2 in human NDs is essentially unknown. Here, we report two rare, non-synonymous (NS), functionally-impairing variants in the KCC2 C-terminal regulatory domain (CTRD) in human ASD (R952H and R1049C) and SCZ (R952H) previously linked with IGE and familial febrile seizures, and another novel NS KCC2 variant in ASD (R1048W) with highly-predicted pathogenicity. Exome data from 2517 simplex families in the ASD Simon Simplex Collection revealed significantly more KCC2 CTRD variants in ASD cases than controls, and interestingly, these were more often synonymous and predicted to disrupt or introduce a CpG site. Furthermore, full gene analysis showed ASD cases are more likely to contain rare KCC2 variants affecting CpG sites than controls. These data suggest genetically-encoded dysregulation of KCC2-dependent GABA signaling may contribute to multiple human NDs.